IMPLEMENTASI ALGORITMA C4.5 UNTUK KLASIFIKASI PRODUK LARIS SEPEDA MOTOR HONDA PADA CV CENDANA MOTOR CEPIRING - Tabitha Salsabilla; Sulastri Sulastri (LPPM Universitas Abdurrab, 2022)
CV Cendana Motor Cepiring is one of the Honda brand motorcycle sales companies in Kendal Regency. Tight motorcycle sales competition requires companies to determine the right sales strategy to increase sales and product marketing in order to attract consumers’ interest. In knowing consumer interest in Honda motorcycle products, research was conducted on predictions of best-selling Honda motorcycle products from each sub-district in Kendal Regency. The research method used is the C4.5 decision tree algorithm with the process using five steps in KDD (Knowledge Discovery in Databases). This research produces a classification with an accuracy of 99% which indicates that the C4.5 algorithm is suitable for measuring the estimated sales of the best-selling Honda motorcycle.